Penerapan Sistem Informasi Posyandu dan Pemantuan Stunting pada Posyandu Indah Sari Kelurahan Manyaran Kota Semarang - Hartono, Budi; Lusiana, Veronica; Wahyuni, Sri; Supriyanto, Aji (Intimas, 2023)
Integrated service posts (Posyandu) are the government's efforts to make it easier for Indonesian people to obtain maternal and child health services. The main activity of posyandu is to record and monitor the nutritional status, growth and development of toddlers. Mitra Posyandu "Indah Sari" in Manyaran sub-district, Semarang city is managed by 10 cadres of local mothers with no less than 50 toddlers who regularly visit this posyandu. The partner's problem is that recording the results of weighing, measuring body length/height, arm circumference (lila) and toddler head circumference (lika), is still recorded in a book or examination card. There is no information system available that makes it easy for posyandu cadres to monitor and provide explanations of the growth and development of toddlers quickly and accurately to parents of toddlers. The Community Service Team provides solutions, (a) development of the Posyandu Information System and Stunting Monitoring (SIP-PS program) and training of Posyandu cadres for SIP-PS operations, as well as (b) counseling by nutritionists about Stunting monitoring and balanced nutritional food. The SIP-PS program can be used according to partners' needs, namely being able to monitor the growth of toddlers more accurately and quickly. "Indah Sari" Posyandu cadres have a good understanding of the importance of monitoring stunting in toddlers.